2014
DOI: 10.1007/s10943-014-9913-4
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Its Relationship with Personality in Depressed People: Preliminary Findings

Abstract: The relationship between spirituality and personality in patients with depression is complex and not much explored. The aim of our study is to examine the interconnection between the spiritual quality of life (QoL) and Cloninger's psychobiological model of personality in patients with depression. The sample consisted of 85 consecutive outpatients treated for depression. The measurements used were: Beck Depression Inventory, WHO-Quality of Life-Spiritual, Religious, Personal Beliefs, and Temperament and Charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A longitudinal study showed that altruism, an aspect of self-transcendence, was associated with resilience in veterans [17] and positive emotions in community volunteers [42]. Self-transcendence and self-directedness were predictors of spiritual QoL in depressed outpatients [73]. Our study points out that some self-transcendent people may see their QoL as satisfactory and be simultaneously symptomatic and resilient [74].…”
Section: Discussionmentioning
confidence: 70%
“…A longitudinal study showed that altruism, an aspect of self-transcendence, was associated with resilience in veterans [17] and positive emotions in community volunteers [42]. Self-transcendence and self-directedness were predictors of spiritual QoL in depressed outpatients [73]. Our study points out that some self-transcendent people may see their QoL as satisfactory and be simultaneously symptomatic and resilient [74].…”
Section: Discussionmentioning
confidence: 70%
“…The service assisted people in talking about their feelings and in playing a greater part in treatment planning with their health care practitioner. Findings from this study add to the growing understanding of the positive association of spiritual issues, where patients who have had their spiritual needs addressed report better mental wellbeing (Wong, Rew and Slaikeu 2006) and similarly report lower levels of depressive symptoms (Mihaljevic´, et al, 2015) therefore CCL can play a useful role in assisting clients who are experiencing depressive conditions.…”
Section: The Effect Of the CCL Felt By Clients After Two Weeksmentioning
confidence: 78%
“…25 In a study with adults on depressive symptoms and religiosity, spirituality and personal beliefs in an outpatient treatment in Croatia, the higher the depression score, the lower the facet scores according to WHOQOL-SRPB. 29 Regarding the findings of WHOQOL-SRPB, the highest score in the Connection with spiritual being or force facet diverged from the validation research of that instrument, in which the highest scores were in the Totality and integration and inner peace among the elders facets; among those without morbidities, the highest score was in the Meaning of Life facet and Faith facet among those with morbidities. 15 The lowest score was identified in the Totality and integration facet, differing from the validation study, in which the lowest scores among healthy and morbidly aged and elderly individuals were, respectively, in the connection with being or spiritual strength facet.…”
Section: Discussionmentioning
confidence: 96%